Sacrificial gate line material paste, perovskite solar cell and preparation method thereof
Patent Information
- Application Number
- CN202611470666.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
AI Technical Summary
(1)热损伤问题:激光脉冲产生的高温会导致钙钛矿层在划线边缘发生热分解,生成 PbI2、PbBr2等副产物
(1)完全避免了激光热损伤,保护了钙钛矿吸光层和顶部电极的完整性;
Smart Images

Figure CN122995497A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solar cells, specifically relating to a sacrificial grid material paste, a perovskite solar cell, and a method for its preparation. Background Technology
[0002] Organic-inorganic hybrid metal halide perovskite solar cells (PSCs) are favored for their excellent photoelectric properties, such as high absorption coefficient (10⁻⁶). 4 -10 5 cm - ¹) Long carrier diffusion length, low recombination rate, and high defect tolerance have made it one of the most promising next-generation photovoltaic technologies. The photoelectric conversion efficiency (PCE) of laboratory-grade small-area perovskite solar cells has exceeded 26%, reaching a performance level comparable to high-end crystalline silicon cells.
[0003] In the process of industrialization, how to scale up small-area, high-efficiency devices from the laboratory to large-area modules while maintaining high conversion efficiency is a core challenge in this field. Currently, the mainstream fabrication process for perovskite photovoltaic modules requires three laser scribing processes (P1 / P2 / P3) to achieve series interconnection of sub-cells. The P1 scribing is used to isolate the transparent conductive oxide (TCO) bottom electrode, the P2 scribing is used to form interlayer conductive channels, and the P3 scribing is used to isolate the top electrode to complete the electrical isolation of adjacent sub-cells. However, in the process of moving from the laboratory to large-scale mass production, a series of problems brought about by the laser scribing process have increasingly become key bottlenecks restricting industrialization.
[0004] While P3 laser marking technology is widely used, it suffers from the following inherent drawbacks that are difficult to overcome: (1) Thermal damage problem: The high temperature generated by the laser pulse will cause the perovskite layer to thermally decompose at the scribing edge, generating byproducts such as PbI2 and PbBr2. These decomposition products will not only become carrier recombination centers, reducing the photoelectric conversion efficiency of the battery, but also accelerate the aging and degradation of the device, seriously affecting the long-term stability of the module; (2) Electrode damage problem: Laser energy is difficult to control precisely, which can easily lead to damage to the bottom film layer, forming a laser-induced periodic surface structure, increasing the series resistance of the electrode, and in severe cases, it can even cause local breakage of the TCO layer, resulting in the failure of electrical connection between sub-cells. (3) High equipment cost: High-precision picosecond or femtosecond lasers are expensive and have high maintenance costs, which increases the production cost of perovskite components. At the same time, the laser scribing process is relatively slow and difficult to be compatible with high-speed roll-to-roll (R2R) production processes; (4) Narrow process window: The quality of laser scribing is very sensitive to parameters such as laser power, scanning speed, and pulse frequency. Even small changes in parameters can lead to a decrease in scribing quality, which increases the difficulty of process control in large-scale production.
[0005] Therefore, there is an urgent need in this field to develop a novel method for preparing P3 streaks. Summary of the Invention
[0006] To address the aforementioned problems in the prior art, this invention proposes a sacrificial material slurry, a perovskite solar cell, and a method for preparing the same.
[0007] Specifically, the present invention provides a sacrificial grid material slurry, the sacrificial grid material slurry comprising a resin, a leveling agent and a solvent, wherein the resin is selected from one or more of polymethyl methacrylate, polystyrene, polyvinyl butyral, fluorinated acrylate copolymers and cellulose derivatives, and the leveling agent is a fluorinated acrylate copolymer leveling agent.
[0008] In one or more embodiments, the mass ratio of the resin to the leveling agent is 100:(0.1-0.3).
[0009] In one or more embodiments, the solid content of the sacrificial grid material slurry is 5wt%-20wt%.
[0010] In one or more embodiments, the cellulose derivative is selected from one or more of ethyl cellulose, cellulose acetate butyrate, hydroxypropyl cellulose, and cellulose diacetate.
[0011] In one or more embodiments, the solvent is selected from one or more of toluene, xylene, ethyl acetate, butyl acetate, hydrofluoroether, and perfluorohexane.
[0012] In some preferred embodiments, the hydrofluoroether is selected from one or both of methyl nonafluorobutyl ether and ethyl nonafluorobutyl ether.
[0013] This invention provides a kit for preparing P3 scribing for perovskite solar cells, the kit comprising the sacrificial grid material slurry and solvent removal as described in any embodiment of this invention.
[0014] In one or more embodiments, the solvent used for removing the sacrificial grid is a solvent capable of dissolving the sacrificial grid formed after the sacrificial grid material paste has been printed and dried.
[0015] In one or more embodiments, the removal solvent is a hydrofluoroether.
[0016] In some preferred embodiments, the removal solvent is selected from one or both of methyl nonafluorobutyl ether and ethyl nonafluorobutyl ether.
[0017] This invention provides a method for preparing perovskite solar cells using a kit according to any embodiment of this invention, the method comprising the following steps: (1) Provide a conductive substrate including a base layer and a conductive layer in contact with the base layer, and use laser technology to cut the conductive substrate to form a P1 scribing line, which penetrates the conductive layer and ends at the base layer. (2) A first charge transport layer and a perovskite light-absorbing layer are sequentially deposited on a conductive substrate with the P1 line; (3) The sacrificial grid material paste is screen-printed on the surface of the perovskite light-absorbing layer and dried to obtain the sacrificial grid; (4) Deposit a second charge transport layer on the surface of the perovskite light-absorbing layer with sacrificial gate lines; (5) A laser process is used to cut from the surface of the second charge transport layer to form a P2 scribing line that penetrates the second charge transport layer, the perovskite light-absorbing layer and the first charge transport layer; (6) Deposit a top electrode on the surface of the second charge transport layer with the P2 scribe line; (7) Remove the sacrificial gate line with a removal solvent to form a P3 scribe line that runs through the top electrode and the second charge transport layer.
[0018] In one or more embodiments, in step (3), the drying temperature is 50-100°C.
[0019] In one or more embodiments, in step (3), the distance between the sacrificial gate line and the P1 scribing line is 170-200 μm.
[0020] In one or more embodiments, in step (3), the thickness of the sacrificial gate line is greater than or equal to the sum of the thicknesses of the subsequently fabricated second charge transport layer and the top electrode.
[0021] In one or more embodiments, in step (3), the width of the sacrificial gate line is 20-200 μm.
[0022] In one or more embodiments, in step (7), the sacrificial grid lines are removed by soaking, spraying, or ultrasonically cleaning the sacrificial grid lines with the removal solvent.
[0023] In one or more embodiments, in step (7), the time for removing the sacrificial gate line is 40-80 seconds.
[0024] In one or more embodiments, in step (7), the width of the P3 line is 20-200 μm.
[0025] In one or more embodiments, in step (7), the distance between the P3 line and the P1 line is 170-200 μm.
[0026] In one or more embodiments, the base layer of the conductive substrate is glass.
[0027] In one or more embodiments, the conductive layer of the conductive substrate is a transparent conductive oxide.
[0028] In one or more embodiments, the width of the P1 scribe line is 0.4-40 μm.
[0029] In one or more embodiments, the method for depositing the first charge transport layer is selected from one or more of magnetron sputtering, atomic deposition, thermal evaporation, and slot coating.
[0030] In one or more embodiments, the thickness of the first charge transport layer is 11-45 nm.
[0031] In one or more embodiments, the method for depositing the perovskite light-absorbing layer is a slot coating method.
[0032] In one or more embodiments, the thickness of the perovskite light-absorbing layer is 400-700 nm.
[0033] In one or more embodiments, the method for depositing the second charge transport layer is selected from one or more of thermal evaporation, magnetron derivatization, atomic deposition, and slot coating.
[0034] In one or more embodiments, the thickness of the second charge transport layer is 20-40 nm.
[0035] In one or more embodiments, the width of the P2 scribe line is 0.5-50 μm.
[0036] In one or more embodiments, the distance between the P2 scribbling line and the P1 scribbling line is 60-110 μm.
[0037] In one or more embodiments, the P2 scribing is located between the P1 scribing and the sacrificial gate line.
[0038] In one or more embodiments, the method for depositing the top electrode is magnetron sputtering.
[0039] In one or more embodiments, the thickness of the top electrode is 100-300 nm.
[0040] The present invention also provides a perovskite solar cell, which is prepared by the method described in any embodiment of the present invention.
[0041] This invention prepares P3 scribings on the surface of a perovskite light-absorbing layer by using screen printing of sacrificial grid material paste to prepare sacrificial grids and removing the sacrificial grids with a removal solvent, thereby replacing the P3 scribings prepared by laser process.
[0042] The preparation method of the present invention has the following advantages: (1) Laser thermal damage is completely avoided, protecting the integrity of the perovskite light-absorbing layer and the top electrode; (2) Reduced equipment costs; the price of screen printing equipment is much lower than that of high-precision lasers. (3) It has good process compatibility and can be seamlessly integrated with existing roll-to-roll continuous production processes; (4) It has a wide process window, making it easy to achieve quality control in large-scale production. Attached Figure Description
[0043] Figure 1 This is a schematic diagram of the perovskite solar cell structure in Embodiment 1 of the present invention.
[0044] Figure 2 The normalized efficiency graphs are for the perovskite solar cells prepared in Example 1 and Comparative Example 1 after 1000 hours of damp heat aging. Detailed Implementation
[0045] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used herein are explained and defined in general terms below. Unless otherwise specified, all technical and scientific terms used herein have the common meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0046] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0047] In this document, the terms “contains,” “includes,” “containing,” and similar terms encompass the meanings of “basically composed of” and “composed of.” For example, when this document discloses “A contains B and C,” “A is basically composed of B and C” and “A is composed of B and C” should be considered as having been disclosed in this document.
[0048] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0049] Unless otherwise specified, percentages refer to mass percentages and proportions refer to mass ratios in this article.
[0050] In this article, the sum of the percentages of all components in the composition is 100%.
[0051] In this document, when describing embodiments or examples, it should be understood that it is not intended to limit the invention to those embodiments or examples. Rather, all alternatives, modifications, and equivalents of the methods and materials described herein are covered within the scope of this invention.
[0052] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0053] One aspect of the present invention provides a sacrificial grid material slurry, comprising a resin, a leveling agent, and a solvent. The resin is selected from one or more of polymethyl methacrylate, polystyrene, polyvinyl butyral, fluorinated acrylate copolymers, and cellulose derivatives. The leveling agent is a fluorinated acrylate copolymer leveling agent.
[0054] The mass ratio of resin to leveling agent in the sacrificial grid material slurry of the present invention can be 100:(0.1-0.3), for example 100:0.1, 100:0.2, 100:0.3.
[0055] The solid content of the sacrificial grid material paste of the present invention can be 5wt%-20wt%, for example 5wt%, 10wt%, 15wt%, 20wt%.
[0056] In this invention, the cellulose derivative may be selected from one or more of ethyl cellulose, cellulose acetate butyrate, hydroxypropyl cellulose, and cellulose diacetate.
[0057] The solvent in the sacrificial grid material slurry of the present invention may be selected from one or more of toluene, xylene, ethyl acetate, hydrofluoroether (HFE) and perfluorohexane.
[0058] In some preferred embodiments, the solvent may be hydrofluoroether, and more preferably, the hydrofluoroether may be selected from one or both of methyl nonafluorobutyl ether and ethyl nonafluorobutyl ether.
[0059] Another aspect of the present invention provides a kit for preparing P3 scribing for perovskite solar cells, the kit comprising the sacrificial grid material paste of the present invention and a solvent removal agent.
[0060] In this invention, the solvent to be removed is a solvent capable of dissolving the sacrificial grid formed by printing and drying the sacrificial grid material slurry of this invention.
[0061] In this invention, the solvent used for removal can be hydrofluoroether.
[0062] In some preferred embodiments, the removal solvent may be selected from one or both of methyl nonafluorobutyl ether (HFE-7100, CAS No. 163702-08-7) and ethyl nonafluorobutyl ether (HFE-7200, CAS No. 163702-06-5).
[0063] The sacrificial gate material paste of the present invention can be formulated into a paste suitable for screen printing (i.e., possessing suitable viscosity, thixotropy, and flowability), and can also be selectively dissolved or swollen and peeled off by hydrofluoroether (HFE) solvents (such as HFE-7100 and HFE-7200). The HFE solvent is chemically inert (orthogonal) to the transparent conductive film layer, the first charge transport layer, the perovskite light-absorbing layer, the second charge transport layer, and the top electrode. Furthermore, the sacrificial gate lines prepared using the sacrificial gate material paste of the present invention can maintain structural and dimensional stability at the process temperatures of subsequent deposition of the second charge transport layer and deposition of the top electrode, and do not undergo harmful chemical reactions with the perovskite layer.
[0064] In this invention, the first charge transport layer can be an electron transport layer and the second charge transport layer can be a hole transport layer; or, the second charge transport layer can be an electron transport layer and the first charge transport layer can be a hole transport layer.
[0065] Another aspect of the present invention provides a method for preparing perovskite solar cells using the kit described herein, comprising the following steps: (1) Provide a conductive substrate including a base layer and a conductive layer in contact with the base layer, and use laser technology to cut the conductive substrate to form a P1 scribing line, the P1 scribing line penetrates the conductive layer and ends at the base layer; (2) A first charge transport layer and a perovskite light-absorbing layer are sequentially deposited on a conductive glass substrate with P1 markings; (3) The sacrificial grid material paste is screen-printed on the surface of the perovskite light-absorbing layer and dried to obtain the sacrificial grid; (4) Deposit a second charge transport layer on the surface of the perovskite light-absorbing layer with sacrificial gate lines; (5) A P2 scribing line is formed by cutting from the surface of the second charge transport layer using laser technology, penetrating the second charge transport layer, the perovskite light-absorbing layer and the first charge transport layer; (6) Deposit a top electrode on the surface of the second charge transport layer with the P2 scribe line; (7) Remove the sacrificial gate line with a removal solvent to form a P3 scribe line that runs through the top electrode and the second charge transport layer.
[0066] In this invention, the base layer of the conductive substrate can be glass, and the conductive layer of the conductive substrate can be a transparent conductive oxide.
[0067] In this invention, the conductive substrate may be selected from one or more of indium tin oxide (ITO) transparent conductive glass, fluorine-doped tin oxide (FTO) transparent conductive glass, tungsten-doped indium oxide (IWO) transparent conductive glass, and aluminum-doped zinc oxide (AZO) transparent conductive glass.
[0068] In this invention, a 1064nm infrared laser can be used to perform laser scribing on a conductive substrate to form P1 scribing lines. The width of the P1 scribing lines can be 0.4-40μm, for example, 0.4μm, 1μm, 2μm, 5μm, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, 25μm, 30μm, 35μm, or 40μm.
[0069] In step (2), the first charge transport layer can be deposited by thermal evaporation, magnetron sputtering, atomic layer deposition, or slot coating. The thickness of the first charge transport layer can be 11-45 nm, for example, 11 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, or 45 nm.
[0070] In some implementations, the first charge transport layer may include a first hole transport layer and a second hole transport layer.
[0071] The thickness of the first hole transport layer can be 10-40nm, for example, 10nm, 20nm, 30nm, or 40nm.
[0072] In some preferred embodiments, the material of the first hole transport layer may be NiOx.
[0073] In some implementations, a slit coating method can be used to prepare the second hole transport layer, and the thickness of the second hole transport layer can be 1-5 nm, such as 1 nm, 2 nm, 3 nm, 4 nm, or 5 nm.
[0074] In some preferred embodiments, the material of the second hole transport layer can be a self-assembled single-molecule material (SAM). Using SAM as the second hole transport layer material serves two purposes: first, it can passivate NiOx surface defects and dangling bonds, suppressing nonradiative recombination at the interface; second, it can optimize interface energy level matching, reduce the hole extraction barrier, and improve charge collection efficiency.
[0075] In some embodiments, the self-assembled monolayer material may be selected from [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACZ), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACZ), [2-(3,6-diphenyl-9H-carbazole-9-yl)ethyl]phosphonic acid (Me-2PACZ), [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid (Me-2PACZ), [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO ... [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid (4PACZ), [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid (MeO-4PACZ), [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid (Me-4PACZ), and (4-(2,7-dibromo-9,9-dimethylacridin-10(9H)yl)butyl)phosphonic acid (DMAcPA) or one or more of these.
[0076] In step (2), a perovskite light-absorbing layer can be prepared by slit coating. The thickness of the perovskite light-absorbing layer can be 400-700 nm, for example, 400 nm, 500 nm, 600 nm, or 700 nm.
[0077] In some implementations, the perovskite structural material raw material can be dissolved in an organic solvent to prepare a perovskite precursor solution, which is then coated and annealed to obtain a perovskite light-absorbing layer.
[0078] In this invention, the perovskite structure material can be of the ABX3 structure, wherein the A ion can be selected from formamidinium cation (FA). + ), Methylammonium cation (MA) + ), cesium ions (Cs) + ), rubidium ions (Rb + ) and guanidine ions (Gua + One or more of the following; B ions are divalent cations, such as lead ions (Pb). 2+ ) or tin ions (Sn 2+ X ions are monovalent anions, including but not limited to iodide ions (I ions). – ), bromide ions (Br) – ), fluoride ions (F) - ), chloride ions (Cl) - ) and cyanate ions (SCN) - One or more of the following.
[0079] In some embodiments, the perovskite structural material is prepared from CsI, FAI, and PbI2, wherein the A-site cation is formed by FAI. + and Cs + Composition, in which FA + The content can be 70%-95%, Cs +The content can be 30%-5% accordingly, with the B-site anion being Pb. 2+ Composition, the X-position anion is composed of I – composition.
[0080] In some implementations, the concentration of the perovskite structure material ABX3 in the precursor solution can be 1 mol / L to 2 mol / L, for example, 1 mol / L, 1.5 mol / L, or 2 mol / L.
[0081] In some embodiments, the solvent for the perovskite precursor solution can be one or both of N,N-dimethylformamide (DMF) and N-methylpyrrolidone (NMP), and when the solvent is a mixed solution of DMF and NMP, the mass content of NMP can be 5%-30%.
[0082] In some implementation schemes, a large-area perovskite light-absorbing layer (≥0.1m) is used. 2 It was prepared by slit coating method.
[0083] In step (3), the sacrificial grid material slurry can be annealed and dried at 50-100℃ to obtain a solid sacrificial grid. Controlling the drying temperature within the above range facilitates solvent evaporation.
[0084] The sacrificial grid line can be located to the right or left of the P1 scribbling line, and the distance between the sacrificial grid line and the P1 scribbling line can be 170-200μm, such as 170μm, 180μm, 190μm, 200μm.
[0085] The thickness of the sacrificial gate line is greater than or equal to the sum of the thicknesses of the subsequently fabricated second charge transport layer and the top electrode.
[0086] In some implementations, the thickness of the sacrificial gate line can be 0.5-5 μm, for example 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm.
[0087] In this invention, the width of the sacrificial gate line can be 20-200μm, for example 20μm, 40μm, 60μm, 80μm, 100μm, 120μm, 140μm, 160μm, 180μm, 200μm.
[0088] In step (4), a second charge transport layer can be deposited using high vacuum thermal evaporation, slit coating, magnetron sputtering, or atomic layer deposition.
[0089] In this invention, the thickness of the second charge transport layer can be 20-40 nm, for example, 20 nm, 30 nm, or 40 nm.
[0090] In some embodiments, the second charge transport layer may be an electron transport layer, and the material of the electron transport layer may be selected from one or more of PCBM ([6,6]-phenyl-C71-isomethyl butyrate), TiO2, SnO2, ZnO2, Al2O3, C60, BCP (2,9-dimethyl-4,7-biphenyl-1,10-o-phenanthroline) and MoOx.
[0091] In step (5), a 532nm green laser can be used to perform laser scribing on the second charge transport to form the P2 scribing line.
[0092] In this invention, the width of the P2 line can be 0.5-50μm, for example 0.5μm, 1μm, 2μm, 5μm, 10μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm.
[0093] In this invention, the distance between the P2 line and the P1 line can be 60-110μm, for example, 60μm, 80μm, 100μm, or 110μm.
[0094] In this invention, the P2 scribing line is located between the P1 scribing line and the sacrificial gate line.
[0095] In step (6), the top electrode can be deposited by magnetron sputtering. The thickness of the top electrode can be 100-300 nm, for example, 100 nm, 150 nm, 200 nm, 250 nm, or 300 nm.
[0096] In this invention, the top electrode can be selected from one or more of Ag, Au, Cu, ITO, IZO, AZO and IWO.
[0097] In step (7), the sacrificial grid lines can be removed by soaking in a solvent, spraying, or ultrasonic cleaning. The removal time can be 40-80s, for example, 40s, 45s, 50s, 55s, 60s, 65s, 70s, 75s, or 80s.
[0098] By controlling the removal time within the above range, the sacrificial grid lines can be completely removed without causing any damage to the perovskite light-absorbing layer, the second charge transport layer, and the top electrode. Furthermore, the open-circuit voltage, short-circuit current density, fill factor, and photoelectric conversion efficiency of the perovskite solar cell can be improved.
[0099] In this invention, the solvent can contact and dissolve the sacrificial gate line through penetration or lateral erosion. After the sacrificial gate line swells or dissolves, the second charge transport layer / top electrode stack above it will mechanically peel off due to loss of support, forming a clean and complete P3 electrical isolation channel (i.e., P3 scribing) in one step.
[0100] In this invention, the width of the P3 line can be 20-200μm, for example 20μm, 40μm, 80μm, 100μm, 120μm, 140μm, 160μm, 180μm.
[0101] In this invention, the depth of the P3 line can be 0.1-5μm, for example 0.1μm, 0.12μm, 0.2μm, 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm.
[0102] In this invention, the distance between the P3 line and the P1 line can be 170-200μm, for example, 170μm, 175μm, 180μm, 185μm, 190μm, 195μm, or 200μm.
[0103] In another aspect, the present invention provides a perovskite solar cell prepared by the above method.
[0104] In some implementations, a perovskite solar cell may include, from bottom to top, a conductive substrate, a hole transport layer, a perovskite light-absorbing layer, an electron transport layer, and a top electrode.
[0105] The perovskite solar cell also includes parallel P3 lines; the P3 lines run through the electron transport layer and the top electrode.
[0106] Furthermore, the P3 streaks are prepared using the kit of the present invention.
[0107] Furthermore, the hole transport layer may include a first hole transport layer and a second hole transport layer.
[0108] In some implementations, the perovskite solar cell also includes parallel-spaced lines P1, P2, and P3.
[0109] The P1 line is prepared using a laser process, is placed on a conductive substrate, penetrates the transparent conductive oxide layer, terminates at the glass substrate, and is embedded in the hole transport layer.
[0110] The P2 scribing is fabricated using laser technology, penetrating the hole transport layer, perovskite light-absorbing layer, and electron transport layer, and is used to embed the top electrode.
[0111] In some implementations, lines P1, P2, and P3 are all perpendicular to the conductive glass substrate, arranged in parallel, with line P2 located between lines P1 and P3.
[0112] In some implementations, the P3 line can be located to the right of the P1 line, and the distance between the P3 line and the P1 line can be 170-200μm, such as 170μm, 180μm, 190μm, or 200μm.
[0113] In some implementations, the P2 line is located to the right of the P1 line, and the distance between the P2 line and the P1 line can be 60-110μm, for example, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 100μm, or 110μm.
[0114] In this invention, the number of lines P1, P2, and P3 is equal. Furthermore, the number of lines P1, P2, and P3 is ≥ 1.
[0115] In this invention, when the number of lines P1, P2, and P3 is all equal to 1, a single perovskite solar cell is obtained; when the number of lines is greater than 1, the large-area perovskite module is divided into N sub-cells by sequentially arranging (lines P1, P2, and P3), (lines P1, P2, and P3)..., and the N sub-cells are connected in series, where N > 1.
[0116] It is understood that, in some embodiments, the number of P1, P2, and P3 lines can be set as needed. The perovskite solar cell is divided into multiple perovskite sub-cells connected in series using multiple P1, P2, and P3 lines, thereby obtaining a large-area perovskite solar cell.
[0117] In this invention, line P1 isolates the transparent conductive oxide layer into multiple mutually insulated sub-units, line P2 realizes the series connection between two adjacent perovskite sub-cells, and line P3 cuts off the top electrode of adjacent sub-cells to achieve electrical isolation of the top electrode, prevent short circuit between units, and complete the division of independent sub-cells.
[0118] In the perovskite solar cell of the present invention, the width of the P3 scribbling line can be 20-200 μm, for example 20 μm, 40 μm, 60 μm, 80 μm, 100 μm, 120 μm, 140 μm, 160 μm, 180 μm, 200 μm.
[0119] In the perovskite solar cell of the present invention, the depth of the P3 scribe line can be 0.1-5 μm, for example 0.1 μm, 0.12 μm, 0.2 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm.
[0120] In the perovskite solar cell of the present invention, the width of the P1 line can be 0.4-40 μm, for example 0.4 μm, 1 μm, 2 μm, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm.
[0121] In the perovskite solar cell of the present invention, the width of the P2 scribe line can be 0.5-50 μm, for example 0.5 μm, 1 μm, 2 μm, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm.
[0122] The beneficial effects of this invention include: (1) This invention eliminates step defects, crystal deterioration and interface damage caused by traditional P3 laser scribing from the root, and completely solves the industry pain point that the scribing area is the core source of component degradation; (2) Avoid thermal damage to the top electrode layer (such as TCO layer) caused by laser scribing. The sacrificial gate line is removed after the top electrode layer sputtering is completed. The top electrode layer has never been directly irradiated by laser, and its transmittance and sheet resistance performance are fully preserved, which is beneficial to the long-term operational stability of the module. (3) It avoids defects such as interface damage and microcracks on the perovskite surface that may be caused by laser scribing, and improves the aging performance of the component in a humid and hot environment, and reduces the long-term operation attenuation rate. (4) The investment cost of screen printing equipment is low, and the operation and maintenance costs are also low. At the same time, the process speed is fast, and continuous production of several meters per minute can be achieved, which significantly improves production efficiency; (5) The solution method used in this invention has good compatibility with all functional layer materials such as perovskite light-absorbing layer, first charge transport layer, second charge transport layer, and electrode, and will not have any negative impact on battery performance.
[0123] The present invention will be described below by way of specific embodiments. It should be understood that these embodiments are merely illustrative and are not intended to limit the scope of the invention. The methods, reagents, and materials used in the embodiments and comparative examples are conventional methods, reagents, and materials in the art, unless otherwise stated. The starting material compounds in the embodiments and comparative examples are all commercially available.
[0124] The fluorinated acrylates used in the examples and comparative examples are fluorinated acrylate copolymers purchased from Shenzhen Zhongfu Technology, with the brand name Fluere 1704 FLZ-Y.
[0125] The fluorinated leveling agent used in the examples and comparative examples was a fluorinated modified acrylate copolymer leveling agent (low polymer grade), purchased from Shenzhen Zhongfu Technology, brand name 3M FC-722.
[0126] Example 1
[0127] Example 1 provides a method for fabricating a perovskite solar cell, the specific steps of which include: (1) Fluorine-doped tin oxide (FTO) transparent conductive glass was used as the conductive substrate (size 300). P1 lines were prepared on a conductive substrate using laser technology. The P1 lines were 40 μm wide and penetrated the transparent conductive oxide (FTO, 400 nm thick) to form equally spaced P1 lines that penetrated the FTO layer. The spacing between the P1 lines was 6 nm. Subsequently, the conductive substrate was ultrasonically cleaned with deionized water, anhydrous ethanol and isopropanol in sequence, and then dried with nitrogen. (2) A first hole transport layer NiOx with a thickness of 25 nm was prepared on a conductive substrate after P1 was scribed by magnetron sputtering. The sputtering temperature was 300 °C, the radio frequency power was 1800 W, and the sputtering gas pressure was 0.5 Pa. (3) MeO-2PACz with a concentration of 1 mg / mL was coated on the surface of the first hole transport layer NiOx by slit coating, and then annealed at a temperature of 100℃ for 10 min to prepare a second hole transport layer with a thickness of 1 nm. (4) After uniformly mixing the perovskite structural material raw materials (FAI, PbI2, MACl and CsI) and organic solvent (the solvent is a mixed solution of DMF and NMP, wherein NMP accounts for 10% of the mass of the mixed solution), a perovskite precursor solution is obtained. 2+ The concentration is 1 mol / L; A perovskite precursor solution was coated onto the second hole transport layer using a slit coating method, followed by annealing at 130℃ for 30 min to prepare a perovskite light-absorbing layer with a thickness of 600 nm. The chemical formula of the perovskite light-absorbing layer is FA. 0.9 Cs 0.1 PbI3; (5) Fluorinated acrylate, fluorinated leveling agent and solvent (HFE7100 and HFE7200 are mixed in a mass ratio of 1:1) are mixed evenly to obtain P3 sacrificial grid slurry, wherein the mass of fluorinated acrylate is 100g, the mass of fluorinated leveling agent is 0.2g and the mass of solvent used is 901.8g; P3 sacrificial gate paste was printed at a predetermined position (170nm to the right of the P1 scribe line) on the surface of the perovskite light-absorbing layer using a screen printing machine. After completion, it was dried at 80℃ for 10 minutes to obtain P3 sacrificial gate lines with a thickness of 2μm and a width of 50μm. (6) C60 and BCP are deposited on the surface of the perovskite layer by high vacuum thermal evaporation to form an electron transport layer with a total thickness of 20 nm (C60 thickness is 15 nm and BCP thickness is 5 nm). P2 lines are prepared on the surface of the electron transport layer by laser process. The width of P2 is 50 μm. The P2 lines penetrate the NiOx layer / self-assembled molecular layer / perovskite light-absorbing layer / C60 layer and BCP layer to form P2 lines with equal spacing that penetrate the NiOx layer / self-assembled molecular layer / perovskite light-absorbing layer / C60 layer and BCP layer. The spacing of P2 lines is 6 mm. P2 is located 110 μm to the right of P1. (7) ITO was deposited on the electron transport layer by magnetron sputtering to form a top electrode layer. The top electrode filled the P2 scribing trench and formed an ohmic contact with the bottom electrode exposed at the bottom of the trench to realize the series electrical connection between adjacent sub-cells. The sputtering temperature was 120℃, the radio frequency power was 900W, the sputtering gas pressure was 0.5Pa, and the thickness was 200nm. (8) Immerse the entire device in a sealed container containing the removal solvent HFE-7100 (methyl nonafluorobutyl ether), and remove the P3 sacrificial gate line after soaking it in the removal solvent for 60s. Then, blow it dry with high-purity nitrogen gas to prepare the P3 scribing line that pierces through the C60 layer, BCP layer and ITO layer at equal intervals. The width of the P3 scribing line is 50μm and it is located 170μm to the right of P1.
[0128] Example 2
[0129] The method for preparing perovskite solar cells in Example 2 is basically the same as that in Example 1, except that in step (5), the mass of fluorinated acrylate is 100g, the mass of fluorinated leveling agent is 0.1g, and the mass of solvent is 900.9g.
[0130] Example 3
[0131] The method for preparing perovskite solar cells in Example 3 is basically the same as that in Example 1, except that in step (5), the mass of fluorinated acrylate is 100g, the mass of fluorinated leveling agent is 0.3g, and the mass of solvent is 902.7g.
[0132] Example 4
[0133] The method for preparing perovskite solar cells in Example 4 is basically the same as that in Example 1, except that in step (8), the soaking time of the P3 sacrificial grid line in the solvent is changed to 40s.
[0134] Example 5
[0135] The method for preparing perovskite solar cells in Example 5 is basically the same as that in Example 1, except that in step (8), the immersion time of the P3 sacrificial grid line in the solvent removal solution is changed to 80s.
[0136] Example 6
[0137] The method for preparing perovskite solar cells in Example 6 is basically the same as that in Example 1, except that in step (5), fluorinated acrylate is replaced with an equal mass of polystyrene (brand name Sigma-Aldrich, high-purity low molecular weight polystyrene Mw=35,000).
[0138] Example 7
[0139] Example 7 describes the preparation of perovskite solar cells in a manner that is essentially the same as in Example 1, except that in step (5), fluorinated acrylate is replaced with an equal mass of ethyl cellulose (brand name: Aqualon EC-N10 Electronics).
[0140] Example 8
[0141] The method for preparing perovskite solar cells in Example 8 is basically the same as that in Example 1, except that in step (5), fluorinated acrylate is replaced with an equal mass of polymethyl methacrylate (brand name MicroChem PMMA 495KA3).
[0142] Example 9
[0143] The method for preparing perovskite solar cells in Example 9 is basically the same as that in Example 1, except that in step (5), fluorinated acrylate is replaced with an equal mass of polyvinyl butyral (Eastman BUTVAR B-03TX).
[0144] Comparative Example 1
[0145] The method for preparing perovskite solar cells in Comparative Example 1 is basically the same as that in Example 1, except that in step (5), P3 sacrificial grid lines are not prepared, and in step (8), P3 lines are prepared on the surface of the top electrode using a 532nm green laser with a laser scribing method. The width of the scribing line is 50μm, and the P3 scribing line is located 170μm to the right of the P1 scribing line. The P3 scribing line pierces through the C60 and BCP layers and the ITO layer, resulting in P3 scribing lines that pierce through the C60 and BCP / ITO layers at equal intervals.
[0146] Comparative Example 2
[0147] The method for preparing perovskite solar cells in Comparative Example 2 is basically the same as that in Example 1, except that in step (5), only fluorinated acrylate and solvent are mixed evenly to obtain P3 sacrificial grid paste.
[0148] Comparative Example 3
[0149] The method for preparing perovskite solar cells in Comparative Example 3 is basically the same as that in Example 1, except that in step (5), the mass of fluorinated acrylate is 100g, the mass of fluorinated leveling agent is 0.5g, and the mass of solvent is 904.5g.
[0150] Comparative Example 4
[0151] The method for preparing perovskite solar cells in Comparative Example 4 is basically the same as that in Example 1, except that in step (8), the soaking time of the P3 sacrificial grid line in the solvent is changed to 20s.
[0152] Comparative Example 5
[0153] The method for preparing perovskite solar cells in Comparative Example 5 is basically the same as that in Example 1, except that in step (8), the soaking time of the P3 sacrificial grid line in the solvent is changed to 100s.
[0154] Comparative Example 6
[0155] The method for preparing perovskite solar cells in Comparative Example 6 is basically the same as that in Example 1, except that in step (5), the mass of fluorinated acrylate is 100g, the mass of fluorinated leveling agent is 0.05g, and the mass of solvent is 900.45g.
[0156] Comparative Example 7
[0157] The method for preparing perovskite solar cells in Comparative Example 7 is basically the same as that in Example 1, except that in step (8), the solvent HFE-7100 is replaced with an equal volume of ethyl acetate.
[0158] Test case
[0159] (a) Performance testing of perovskite solar cells
[0160] At 25℃, AM1.5G standard solar spectrum, and irradiance of 1000W / m² 2 Using a solar simulator with the voltage range set to -0.2 to 15V, the performance (open-circuit voltage, short-circuit current density, fill factor, and photoelectric conversion efficiency) of the perovskite solar cells in Examples 1-9 and Comparative Examples 1-7 were measured. The specific results are shown in Table 1.
[0161] (1) Open circuit voltage (Voc): The voltage value when the current is zero.
[0162] (2) Short-circuit current density (Jsc): The current value when the voltage is zero is the short-circuit current (Isc), and the current on a unit cell surface area is the short-circuit current density.
[0163] (3) Fill factor (FF): The ratio of the battery's maximum output power (Pmax) to the product of the open-circuit voltage and the short-circuit current. The formula is (Pmax / Voc) Isc), where the maximum power point is the point where the battery output power reaches its maximum value.
[0164] (4) Photoelectric conversion efficiency (PCE): Photoelectric conversion efficiency refers to the ratio of maximum output power to incident light power (Pin), and the calculation formula is (Pmax / Pin). 100%.
[0165] (ii) Normalized efficiency test after damp heat aging
[0166] The damp heat aging test method for perovskite solar cells is as follows: Using a solar simulator and IV testing system, the battery was measured under standard test conditions (AM1.5G standard solar spectrum at 25 °C, incident light power Pin of 100 mW / cm²). 2 The initial photoelectric conversion efficiency (PCE0) was measured within a voltage range of -0.2 V to 1.5 V and used as the reference efficiency. The batteries were then subjected to damp heat aging in a controlled temperature and humidity environment (85℃±2℃, 85%±5% RH, dark environment, no external bias). During the aging process, the damp heat aging was interrupted at predetermined time points (every 200 hours), and the batteries were removed and their current aging efficiency (PCE0) was measured. t The total duration is 1000 hours.
[0167] (1) Reference efficiency (PCE0): The initial efficiency of the battery before aging; (2) Aging efficiency (PCE) t ): The efficiency of the battery measured after damp heat aging for t time; (3) Normalized efficiency: The ratio of aging efficiency PCEt to baseline efficiency (PCE0), calculated using the formula (PCE0 / PCE0). t / PCE0) 100%; (4) Attenuation curve: The normalized efficiency is calculated for each time point, and finally an attenuation curve of normalized efficiency over time is obtained to evaluate the damp heat stability of the battery.
[0168] The normalized efficiencies of the perovskite solar cells prepared in Example 1 and Comparative Example 1 after aging are shown in Table 2.
[0169] A schematic diagram of the perovskite solar cell prepared in Example 1 is shown below. Figure 1 As shown.
[0170] The normalized efficiency graphs of the perovskite solar cells prepared in Example 1 and Comparative Example 1 after 1000 hours of damp heat aging are shown in the figure. Figure 2 As shown.
[0171] Table 1: Open-circuit voltage, short-circuit current density, fill factor, and photoelectric conversion efficiency of perovskite solar cells prepared in Examples 1-9 and Comparative Examples 1-7
[0172] Table 2: Normalized efficiency of perovskite solar cells prepared in Example 1 and Comparative Example 1 after aging
[0173] As can be seen from the experimental results of Examples 1-3, Comparative Examples 2 and 6 in Table 1, when the content of fluorinated leveling agent is low, the surface tension of pure fluorinated acrylate slurry will be higher than that of perovskite surface, and it will not be able to spread effectively on perovskite surface. At the same time, the surface tension gradient generated during solvent evaporation will cause serious edge jaggedness, high-frequency shrinkage and wire breakage problems in sacrificial grid lines. These morphological defects will directly reduce the geometric fill factor of the component.
[0174] As shown in Table 1, the experimental results of Examples 1-3 and Comparative Example 3 indicate that when the fluorine leveling agent content is too high, the surface tension of the sacrificial grid slurry will drop to an excessively low level, leading to over-spreading of the sacrificial grid lines and linewidth exceeding the design range, which in turn causes a decrease in the geometric fill factor. Simultaneously, excessive leveling agent will accumulate at the interface between the perovskite and sacrificial grid lines, forming a low-adhesion isolation layer. This makes the sacrificial grid lines prone to warping and detachment during subsequent coating processes, ultimately resulting in a short circuit in the sub-cell caused by the TCO layer covering the bottom of the isolation line.
[0175] As shown in Table 1, the experimental results of Examples 1, 4, and 5 and Comparative Examples 4-5 indicate, if the solvent soaking time is too short, the solvent cannot fully penetrate into the sacrificial grid to complete the dissolution process, and can only remove part of the surface material. This results in ineffective electrical isolation between adjacent sub-cells, leading to severe leakage or even short circuits. Although prolonged solvent soaking can completely remove the sacrificial grid, the functional layers of the perovskite solar cell are not absolutely dense and contain tiny pores. Solvent removal may damage the connections between the film layers, causing slight delamination at the interface. These changes increase interfacial recombination of charge carriers, leading to a decrease in open-circuit voltage and fill factor. At the same time, the increase in interface resistance raises the series resistance of the device.
[0176] As can be seen from the experimental results of Examples 1, 6-9 and Comparative Example 7 in Table 1, the perovskite solar cells prepared using the sacrificial grid material paste of the present invention have good overall performance.
[0177] As shown in Table 2, the experimental results of Example 1 and Comparative Example 1 reveal that the instantaneous high temperature generated by the laser pulse causes thermal decomposition of the perovskite layer at the scribing edge, generating unstable byproducts such as PbI2. These substances serve as both carrier recombination centers and initiation sites for device aging. Simultaneously, the laser-induced heat-affected zone disrupts the perovskite's crystalline structure, leading to microcracks and interface delamination between functional layers, providing pathways for the intrusion of moisture and oxygen. Furthermore, the laser energy is difficult to precisely control, easily causing over-etching of the bottom perovskite layer and damage to the top TCO electrode, forming hidden leakage channels. These defects continuously expand under long-term illumination and electric field effects, ultimately leading to accelerated device performance degradation.
Claims
1. A sacrificial grid material paste, characterized in that, The sacrificial grid material slurry includes a resin, a leveling agent, and a solvent. The resin is selected from one or more of polymethyl methacrylate, polystyrene, polyvinyl butyral, fluorinated acrylate copolymers, and cellulose derivatives. The leveling agent is a fluorinated acrylate copolymer leveling agent.
2. The sacrificial grid material paste as described in claim 1, characterized in that, The mass ratio of the resin to the leveling agent is 100:(0.1-0.3).
3. The sacrificial grid material paste as described in claim 1, characterized in that, The solid content of the sacrificial grid material slurry is 5wt%-20wt%.
4. The sacrificial grid material paste as described in claim 1, characterized in that, The cellulose derivative is selected from one or more of ethyl cellulose, cellulose acetate butyrate, hydroxypropyl cellulose, and cellulose diacetate.
5. The sacrificial grid material paste as described in claim 1, characterized in that, The solvent is selected from one or more of toluene, xylene, ethyl acetate, butyl acetate, hydrofluoroether, and perfluorohexane.
6. The sacrificial grid material paste as described in claim 5, characterized in that, The hydrofluoroether is selected from one or both of methyl nonafluorobutyl ether and ethyl nonafluorobutyl ether.
7. A kit for preparing P3 lines for perovskite solar cells, characterized in that, The kit comprises the sacrificial grid material slurry and the removal solvent as described in any one of claims 1-6.
8. The kit according to claim 7, characterized in that, The solvent used for removing the sacrificial grid is a solvent capable of dissolving the sacrificial grid formed after the sacrificial grid material slurry has been printed and dried.
9. The kit according to claim 7, characterized in that, The removal solvent is hydrofluoroether.
10. The kit according to claim 9, characterized in that, The removal solvent is selected from one or both of methyl nonafluorobutyl ether and ethyl nonafluorobutyl ether.
11. A method for preparing perovskite solar cells using the kit according to any one of claims 7-10, characterized in that, The method includes the following steps: (1) Provide a conductive substrate including a base layer and a conductive layer in contact with the base layer, and use laser technology to cut the conductive substrate to form a P1 scribing line, which penetrates the conductive layer and ends at the base layer. (2) A first charge transport layer and a perovskite light-absorbing layer are sequentially deposited on a conductive substrate with the P1 line; (3) The sacrificial grid material paste is screen-printed on the surface of the perovskite light-absorbing layer and dried to obtain the sacrificial grid; (4) Deposit a second charge transport layer on the surface of the perovskite light-absorbing layer with sacrificial gate lines; (5) A laser process is used to cut from the surface of the second charge transport layer to form a P2 scribing line that penetrates the second charge transport layer, the perovskite light-absorbing layer and the first charge transport layer; (6) Deposit a top electrode on the surface of the second charge transport layer with the P2 scribe line; (7) Remove the sacrificial gate line with a removal solvent to form a P3 scribe line that runs through the top electrode and the second charge transport layer.
12. The method as described in claim 11, characterized in that, Step (3) of the method has one or more of the following characteristics: The drying temperature is 50-100℃; The distance between the sacrificial grid line and the P1 scribing line is 170-200μm; The thickness of the sacrificial gate line is greater than or equal to the sum of the thicknesses of the subsequently fabricated second charge transport layer and the top electrode; The width of the sacrificial gate line is 20-200 μm.
13. The method as described in claim 11, characterized in that, Step (7) of the method has one or more of the following characteristics: The sacrificial grid lines can be removed by soaking, spraying, or ultrasonically cleaning them with the aforementioned removal solvent. The time to remove the sacrificial gate is 40-80 seconds; The width of the P3 scribe line is 20-200μm; The distance between the P3 line and the P1 line is 170-200 μm.
14. The method as described in claim 11, characterized in that, The method has one or more of the following characteristics: The base layer of the conductive substrate is glass; The conductive layer of the conductive substrate is a transparent conductive oxide; The width of the P1 line is 0.4-40 μm; The method for depositing the first charge transport layer is selected from one or more of magnetron sputtering, atomic deposition, thermal evaporation, and slot coating. The thickness of the first charge transport layer is 11-45 nm; The method for depositing the perovskite light-absorbing layer is the slot coating method; The thickness of the perovskite light-absorbing layer is 400-700 nm; The method for depositing the second charge transport layer is selected from one or more of the following: thermal evaporation, magnetron derivatization, atomic deposition, and slot coating. The thickness of the second charge transport layer is 20-40 nm; The width of the P2 scribe line is 0.5-50 μm; The distance between the P2 line and the P1 line is 60-110 μm; The P2 scribing line is located between the P1 scribing line and the sacrificial gate line; The method for depositing the top electrode is magnetron sputtering; The thickness of the top electrode is 100-300 nm.
15. A perovskite solar cell, characterized in that, The perovskite solar cell is prepared by the method described in any one of claims 11-14.